Diagnosis and Assessment of Apathy in Elderly Chinese Patients With Cerebral Small Vessel Disease - Zhào, Hóngyi; Liu, Yu; Xia, Zhenxi; Xie, Hongyang; Huang, Yonghua (Frontiers in Psychiatry, 2021)
Objective: The study aimed to estimate the frequency of apathy in Chinese patients with Cerebral small vessel disease (CSVD) and investigate the relationship between apathy and neuroimaging markers of CSVD. Methods: 150 CSVD aged patients were recruited for a cross-sectional observational study. Following the new revised version of diagnostic criteria for apathy (DCA), each patient was evaluated successively by the Neuropsychiatric Inventory (NPI-apathy), Geriatric Depression Scale (GDS) and Caregiver Burden Scale (CBS). The MRI presence of lacunes, white matter hyperintensities, cerebral microbleeds, and perivascular spaces were rated independently. Furthermore, presence of all these MRI markers were summed in a score of 0-4 representing all CSVD features combined. Results: According to the DCA, we found that the frequency of apathy in Chinese AD patients reached 37.33%, with the lack and diminished goal-directed activities in dimension of Behavior/Cognition. We found a close relationship between apathy and depression. Caregiver burden was positively correlated with apathy severity. Apathy, but not depression, was positively associated with total CSVD burden, rather than separate MRI marker of CSVD. Conclusion: As a key component of neuropsychiatric symptom, apathy was common in Chinese elderly with CSVD, more attention should be paid to apathy in clinical practice of CSVD.